Role of DNA Replication Proteins in Double-Strand Break-Induced Recombination in Saccharomyces cerevisiae - Wang, Xuan (American Society for Microbiology, 2004)
Mitotic double-strand break (DSB)-induced gene conversion involves new DNA synthesis. We have analyzed the requirement of several essential replication components, the Mcm proteins, Cdc45p, and DNA ligase I, in the DNA synthesis of Saccharomyces cerevisiae MAT switching. In an mcm7-td (temperature-inducible degron) mutant, MAT switching occurred normally when Mcm7p was degraded below the level of detection, suggesting the lack of the Mcm2-7 proteins during gene conversion. A cdc45-td mutant was also able to complete recombination. Surprisingly, even after eliminating both of the identified DNA ligases in yeast, a cdc9-1 dnl4Δ strain was able to complete DSB repair. Previous studies of asynchronous cultures carrying temperature-sensitive alleles of PCNA, DNA polymerase α (Polα), or primase showed that these mutations inhibited MAT switching (A. M. Holmes and J. E. Haber, Cell 96:415-424, 1999). We have reevaluated the roles of these proteins in G(2)-arrested cells. Whereas PCNA was still essential for MAT switching, neither Polα nor primase was required. These results suggest that arresting cells in S phase using ts alleles of Polα-primase, prior to inducing the DSB, sequesters some other component that is required for repair. We conclude that DNA synthesis during gene conversion is different from S-phase replication, involving only leading-strand polymerization.